Updates on the relationship insomnia and hypertension in the elderly - Freitas, Lucas Zanon de (2021)
Introduction: Insomnia is defined as a persistent difficulty with the onset, duration, consolidation or quality of sleep. This disorder has been studied as a possible predisposing factor for Cardiovascular Disease (CVD) and Systemic Arterial Hypertension (SAH), mainly affecting the elderly, since hypertension and insomnia are more prevalent in this age group. Objective: This article aims to develop a literary review on the association between insomnia and hypertension, in an elderly population, in search of a possible relationship between cause and effect. Methodology: A search for articles, published in the last 5 years, in the VHL and LILACS databases, in Portuguese and English, using the descriptors insomnia, hypertension and elderly, was carried out. Results: There are similarities between the pathophysiology of Insomnia and SAH. Three theories propose to explain this relationship, the psychogenic, the neurological and the mood mismatch, which cause neurological and hormonal dysfunctions. Conclusion: It was found that there is still no consensus among the studies, despite some pathophysiological, epidemiological and clinical relationships between SAH and Insomnia, since research is still recent and evolving.